2016
DOI: 10.7860/jcdr/2016/24175.8922
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorder, Gastrointestinal Problems and Behaviour Problems Seen in Autism Spectrum Disorder Children and Yoga as Therapy: A Descriptive Review

Abstract: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder with deficiencies in many developmental milestones during the infantile childhood. Recent researches have shown that apart from behaviour problems, the ASD children also suffer from physiological conditions such as disturbed sleep and gastrointestinal problems that could be the contributing factors to their daytime behaviour problems. Lots of parents have expressed that, lack of sleep among the children have resulted in high levels of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Autism spectrum disorder (ASD) is considered as a relatively serious developmental disorder in brain [1], usually congenital and found in early childhood development [2, 3]. It is currently one of the most severe childhood psychiatric diseases, which mainly manifested in social and communication dysfunction [4], language dysfunction [5], and repetitive ritualized stereotypes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is considered as a relatively serious developmental disorder in brain [1], usually congenital and found in early childhood development [2, 3]. It is currently one of the most severe childhood psychiatric diseases, which mainly manifested in social and communication dysfunction [4], language dysfunction [5], and repetitive ritualized stereotypes [6].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms not only aggravate the symptoms of autism itself but also lead to other behavioral problems [34]. ASDs can be categorized as the "Yu" differentiation grouping of TCM.…”
Section: Discussionmentioning
confidence: 99%
“…Among these characteristics, loss of appetite and GI problems are common with this constitution, which shows features that are similar to the typical symptoms of autism. These symptoms not only aggravate the symptoms of autism itself but also lead to other behavioral problems [ 34 ]. ASDs can be categorized as the “ Yu ” differentiation grouping of TCM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ASD associated with intellectual disability often have a pre-existing sleep disorder. [ 1 4 , 18 20 ] It has been suggested that insomnia symptoms of sleep problems, such as increased sleep onset latency, increased wake after sleep onset episodes, and reduced total sleep time, are commonly experienced with ASD. [ 14 , 15 ] Therefore, we consider that daily medication with these drugs for maintenance of mental condition might have a major influence on sleep quality.…”
Section: Discussionmentioning
confidence: 99%